Multilayer Films Based on Chitosan/Pectin Polyelectrolyte Complexes as Novel Platforms for Buccal Administration of Clotrimazole - Joanna Potaś; Emilia Szymańska; Magdalena Wróblewska; Izabela Kurowska; Mateusz Maciejczyk; Anna Basa; Eliza Wolska; Agnieszka Zofia Wilczewska; Katarzyna Winnicka (MDPI AG, 2021)
Buccal films are recognized as easily applicable, microbiologically stable drug dosage forms with good retentivity at the mucosa intended for the therapy of oromucosal conditions, especially infectious diseases. Multilayer films composed of layers of oppositely charged polymers separated by ionically interacting polymeric chains creating polyelectrolyte complexes represent very interesting and relatively poorly explored area. We aimed to develop the antifungal multilayer systems composed of cationic chitosan and anionic pectin as potential platforms for controlled delivery of clotrimazole. The systems were pharmaceutically characterized with regard to inter alia their release kinetics under different pH conditions, physicomechanical, or mucoadhesion properties with using an animal model of the buccal mucosa. The antifungal activity against selected Candida sp. and potential cytotoxicity with regard to human gingival fibroblasts were also evaluated. Interactions between polyions were characterized with Fourier transform infrared spectroscopy. Different clotrimazole distribution in the films layers highly affected their in vitro dissolution profile. The designed films were recognized as intelligent pH-responsive systems with strong antifungal effect and satisfactory safety profile. As addition of chitosan resulted in the improved antifungal behavior of the drug, the potential utilization of the films in resistant cases of oral candidiasis might be worth of further exploration.